Mitogenic, chemotactic, and synthetic responses of rat periodontal ligament fibroblastic cells to polypeptide growth factors in vitro - Matsuda, N; Lin, W L; Kumar, N M; Cho, M I; Genco, R J (Journal of periodontology (1970), 1992)
The mitogenic, chemotactic, and synthetic responses of rat periodontal ligament (PDL) fibroblastic cells to epidermal growth factor (EGF), transforming growth factor-beta (TGF-beta), recombinant human platelet-derived growth factor (rhPDGF)-AB, rhPDGF-BB, natural (n) PDGF-AB, and insulin-like growth factor-I (IGF-I) were examined in vitro using PDL cells obtained from the coagulum of healing tooth sockets. PDGFs and IGF-I have potent and comparable mitogenic effects on PDL fibroblastic cells. The maximum mitogenic effect of PDGFs was observed at the concentration of 10 ng/ml, whereas that of IGF-I was seen at concentrations higher than 100 ng/ml. In contrast, EGF induced moderate, and TGF-beta inhibitory mitogenic responses. The combination of rhPDGF-AB with either EGF or TGF-beta demonstrated comparable mitogenic potency, equivalent to the level of PDGF alone regardless of the mitogenic effect of other growth factors. The combination of rhPDGF-AB and IGF-I, however, showed a synergistic effect revealing the highest mitogenic effect among all individual growth factors as well as any combinations of the growth factors tested. Similarly, PDL fibroblastic cells demonstrated strong chemotactic responses to both IGF-I and PDGFs. The maximum effect was observed by IGF-I at concentrations higher than 10 ng/ml, followed by rhPDGF-BB at 0.1 ng/ml, rhPDGF-AB and nPDGF at concentrations ranging from 0.1 to 1 ng/ml. TGF-beta revealed no, and EGF slightly increased, chemotactic effects. IGF-I slightly enhanced the synthesis of total protein, whereas other factors had no significant effect. However, both rhPDGF-AB and TGF-beta stimulated collagen synthesis. On the other hand, IGF-I showed no effect on collagen synthesis, while EGF suppressed collagen synthesis. These findings suggest that rhPDGF-BB and IGF-I stimulate proliferation and chemotaxis of PDL fibroblastic cells. In addition, the combination of these growth factors further increases the mitogenic effect. rhPDGF-AB also stimulates collagen synthesis by PDL fibroblastic cells. Thus, rhPDGF-BB and IGF-I may have important roles in promotion of PDL healing, and consequently, may be useful for clinical application in periodontal regenerative procedures.